Experimental analysis of the V-Charge variable drive supercharger system on a 1.0 L GTDI engine. (March 2018) - Hu, Bo; Akehurst, Sam; Lewis, Andrew GJ; Lu, Pengfei; Millwood, Darren; Copeland, Colin; Chappell, Edward; De Freitas, Andrew; Shawe, James; Burtt, Dave
A compound charging system that pairs a turbocharger with a supercharger seems to be a potential trend for future passenger car gasoline engines, as the strength of both could be enhanced and the deficiencies of each could be offset. The use of a fixed-ratio positive-displacement supercharger system on a downsized turbocharged gasoline engine has already appeared on the market. Although such systems can achieve enhanced low-end torque and improved transient response, several challenges still exist. An alternative solution to the fixed-ratio positive-displacement supercharger is the V-Charge variable ratio centrifugal supercharger. This technology utilizes a Torotrak continuously variable transmission (CVT) coupled to a centrifugal compressor for near silent boosting. With a wide ratio spread of 10:1 and rapid rate of ratio change, the compressor speed can be set independently of the engine speed to provide an exact boost pressure for the required operating points, without the need to recirculate the air through a bypass valve. A clutch and an active bypass valve can also be eliminated, due to the CVT capability to down-speed, thus improving the noise vibration and harshness performance. This paper will, for the first time, present and discuss the V-Charge technology optimization and experimental validation on a 1.0 L GTDI engine to achieve a better brake specific fuel consumption and transient response over the turbo-only and the fixed-ratio positive-displacement supercharger solution. The potential for the V-Charge system to increase the low-end torque and enable a down-speeding strategy is also discussed.